Task and data allocation in autonomous mobile robots - Tan, Natasha Zhaowen (Nanyang Technological University, 2024)
The increasing need for AMR in service industries, particularly those requiring precision and efficiency, such as coffee preparation, emphasizes the importance of advanced task and data allocation methods that improve system performance and adaptability. Service-oriented AMRs have to navigate environments that demand not only operational efficiency but also the capacity to interact dynamically with complex, ever-changing environments and customer needs.